Origin of accessory left hepatic artery from left gastric artery - Chaitra, B.R.; Dakshayani, K.R. (International Journal of Research in Medical Sciences, 2017)
Liver is supplied by the branches of celiac trunk. Common hepatic artery which is a branch of celiac trunk continues as proper hepatic artery after giving gastroduodenal artery. Proper hepatic artery enters the liver at Porta hepatis after diving into right and left hepatic artery. The knowledge of branching patterns of arteries and their variations is important in various surgical and radiological procedures. During routine dissection conducted in the Department of Anatomy, MMC&RI, Mysore, an accessory left hepatic artery was seen arising from left gastric artery in an elderly male cadaver aged around 60 years. An accessory left hepatic artery was arising from left gastric artery and was entering the left lobe of liver. In less than 1% of cases, the accessory left hepatic artery supplies the part of left lobe of liver or whole liver. Knowledge of anomalous origin of left hepatic artery is important for successful liver transplant surgeries, hepatobiliary operations, gastrectomies, hiatal surgery for gastro esophageal reflex, bariatric surgeries and in selective arterial chemotherapy for liver cancers. Ligation or laceration of this artery during surgeries causes fatal ischemic necrosis of left lobe of liver.